MAGNETOROTATIONAL SUPERNOVAE AND MAGNETO-DIFFERENTIAL-ROTATIONAL INSTABILITY - Moiseenko, S. G.; Bisnovatyi-Kogan, G. S. (Одеські астрономічні публікації, 2013)
Results of simulations of magne torotational(MR) core-collapse supernova explosion mechanism are presented. For the simulations we have used specially developed Lagrangian completely conservative operator-difference scheme on triangular grid of variable structure. 2D numerical simulations show that the Magneto-Differential-Rotational Instability (MDRI) (Tayler-type instability) develops which leads to the exponential growth of all components of magnetic field. The instability reduces time evolution of the MR explosion. The explosion energy found in MR explosion corresponds to observations. We made simulations of the MR mechanism supernova explosion with different equations of state and different procedures of neutrino transport. We found that the results of the MR explosion does not significantly change